UNDERGRADUATE STUDENTS' MOTIVATION ON ENGLISH LANGUAGE LEARNING AT UNIVERSITAS TEKNOKRAT INDONESIA - Wulandari Pranawengtias (fsip.teknokrat.ac.id, 2022)
AbstractThe purpose of this research is to identify the factors that influence the learning motivation of Universitas Teknokrat Indonesia students. It also aims to reveal the motivational sub-factors that affect the student learning process. This study uses a qualitative research method used questionnaire consisting of 2 intrinsic motivation factors and 3 extrinsic motivation factors, with a total of 30 questions. Questionnaire in the form of 5 Likert Scale. The sample amounted to 30 students from the majors in sports education, mathematics education, and English education. Data from the questionnaire were analyzed using statistical procedures and described descriptively. The results showed that extrinsic motivation contributed more to students' learning motivation (39.66) compared to intrinsic factors (36.1). The results also show that the extrinsic motivation factor; giving rewards and punishments (41.4) as well as the quality of lecturers and the teaching and learning process (40.0) are the two dominant factors that can increase students' learning motivation. Thus, these results have implications for what to pay attention to in language learning, especially in learning English. Therefore, the appropriateness of giving rewards or punishments for students and the quality of lecturers must be improved because it will increase student motivation in language learning.